Global Dual Sourcing and Order Smoothing: The Impact of Capacity and Lead Times - Boute, Robert N.; Van Mieghem, Jan A. (Management Science, 2015)
After decades of offshoring production across the world, companies are rethinking their global networks. Local sourcing is receiving more attention, but it remains challenging to balance the offshore sourcing cost advantage against the increased inventories, because of its longer lead time, and against the cost and (volume) flexibility of each source’s capacity. To guide strategic allocation in this global network decision, this paper establishes reasonably simple prescriptions that capture the key drivers. We adopt a conventional discrete-time inventory model with a linear control rule that smoothes orders and allows an exact and analytically tractable analysis of single- and dual-sourcing policies under normal demand. Distinguishing features of our model are that it captures each source’s lead time, capacity cost, and flexibility to work overtime. We use Lagrange’s inversion theorem to provide exact and simple square-root bound formulae for the strategic sourcing allocations and the value of dual sourcing. The formulae provide structural insight on the impact of financial, operational, and demand parameters, and a starting point for quantitative decision making. We investigate the robustness of our results by comparing the smoothing policy with existing single- and dual-sourcing models in a simulation study that relaxes model assumptions. This paper was accepted by Yossi Aviv, operations management.